Educational Governance and Policy Implementation in Conflict-Affected Contexts: The Case of Hadhramout, Yemen - Al-Hendi, Naa'ma M (AUC Knowledge Fountain, 2026)
Education remains a vital component of societal resilience and development in a world increasingly defined by conflict and instability. Education during conflict is crucial for academic learning and providing essential life skills and psychosocial support to children affected by war. Yemen is being plagued by political upheaval and a lack of economic flow to keep education running efficiently. Although Hadhramout, a governorate in Yemen, remains relatively stable, its education sector continues to face persistent challenges that hinder the quality and effectiveness of education. This study investigates the key challenges facing K-12 education in Hadhramout and examines the extent to which government interventions have addressed these issues to sustain educational provision. Employing a qualitative case study design, the research draws on 31 semi-structured interviews with teachers, principals, educational supervisors, government officials, and union representatives. The findings of the research revealed that economic decline and conflict pressures compromised the quality of education, along with internal displacement and pressure on education services. The study also revealed that Hadhramout faces challenges, including resource and infrastructure constraints, capacity and professional development challenges, outdated curriculum, teachers’ strike, and weak academic governance and evaluation integrity. Although educational offices have implemented initiatives in coordination with local authorities and international organizations to mitigate some of these issues, their impact has been constrained by governance deficits, corruption, and top-down policymaking that excludes street-level educators from decision-making processes. The thesis concludes with policy recommendations to strengthen educational governance, improve teacher capacity, and promote equitable, sustainable reform in Yemen’s fragile context.